'Sex isn't better than love': Exploring South African Indian teenage male and female desires beyond danger. (August 2016) - Bhana, Deevia
This article analyses how South African Indian teenage men and women conceptualise desire, sex and love, their resistance to and accommodation of gender inequalities within relationship dynamics. It calls attention to a reconceptualisation of childhoods that extends agency to sexuality beyond a preoccupation with sexual danger. By focusing on the diversity of sexual meanings, attention is given to the plurality of childhood sexual experiences among South African Indian teenagers. Finally, the article argues that deeper insight into teenage pleasure and power can sharpen interventions that promote healthy teenage sexualities.